Tantangan dan Solusi Memahami Mahram di Era Modern - Sri Mulyani; Shifa Azzahra; Tsania Tazlila Wardanu; Revi Yulianti; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The background of this study focuses on the understanding of the concept of mahram in the context of increasingly complex modern life. Social, cultural, and technological changes are influencing how individuals understand and apply the values of mahram in their daily interactions. The aim of this research is to identify the challenges faced by society in understanding mahram and to offer practical solutions to address these issues. The research method employed is a qualitative approach, utilizing in-depth interviews and content analysis of various literature sources, as well as surveys conducted among the community. The collected data is analyzed to identify patterns and key issues related to the understanding of mahram. The results of the discussion indicate that the main challenges in understanding mahram in the modern era include a lack of consistent understanding, the influence of social media, and shifts in social norms. Proposed solutions include enhancing religious education, public awareness campaigns, and utilizing digital platforms to disseminate accurate information about mahram. This research is expected to contribute to society's efforts in strengthening the understanding of mahram that is relevant to the current context.